2012
DOI: 10.1080/15685551.2012.705491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel poly(ester amine) dendrimers by Michael addition and acrylate esterification

Abstract: Dendrimers are a new kind of polymers. They have gained widespread attentions due to their remarkable properties in recent years. In the present work, a facile and efficient synthetic approach to prepare poly(ester amine) dendrimers is presented. Three different generations of poly(ester amine) dendrimers are synthesized starting from using pentaerythritol tetraacrylate as a core, followed by Michael addition and acrylate esterification reactions. This synthetic protocol is highly efficient, high yielding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The peaks at 1128.2 cm −1 (C-O symmetric stretching) and 1046.3 cm −1 (asymmetric stretching) are the characteristic absorption bonds of hyperbranched polyester. [15,16] …”
Section: Measurementsmentioning
confidence: 98%
“…The peaks at 1128.2 cm −1 (C-O symmetric stretching) and 1046.3 cm −1 (asymmetric stretching) are the characteristic absorption bonds of hyperbranched polyester. [15,16] …”
Section: Measurementsmentioning
confidence: 98%
“…It is often used in the synthesis of dendrimers via several steps in organic solution. The prepared dendrimers show promising applications in coatings, drug, gene delivery, nanotechnology, and supramolecular science due to their unique chemical and physical properties. , …”
Section: Introductionmentioning
confidence: 99%
“…The prepared dendrimers show promising applications in coatings, drug, gene delivery, nanotechnology, and supramolecular science due to their unique chemical and physical properties. 16,17 In this paper, a simple method is described to synthesize cPAs through a Michael ene-amine addition followed with bulk polycondensation. A Michael addition reaction of methyl acrylate (MA) with 1,6-hexanediamine (HDA) was conducted in bulk state at mild conditions, and a hexanediamine-tetraester (HDATE) was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 1718.9 cm −1 (CO stretching vibration), 1128.1 cm −1 (CO symmetric stretching), and 1042.5 cm −1 (asymmetric stretching) were the characteristic absorption bands of polyester. From above analysis, it can be concluded that the different generation hyperbranched polyester were successfully synthesized .…”
Section: Resultsmentioning
confidence: 94%
“…Due to the unique structure of hyperbranched polymers, they have been usually used as templates for synthesis of metal nanoparticles. Sun et al synthesized silver nanoparticles using methoxycarbonyl‐terminated hyperbranched poly(amine‐ester) as templates; Zhang et al prepared colloid silver nanoparticles using hyperbranched poly(amidoamine) as the stabilizer; and Mahapatra and Karak synthesized silver nanoparticle in DMSO solution in the presence of hyperbranched polyamine. Although all kinds of metal nanoparticles have been synthesized by using this method, to the best of our knowledge, the application of hyperbranched polymers in preparing polymer/metal nanoparticle composites has been reported by few researchers.…”
Section: Introductionmentioning
confidence: 99%